2019
DOI: 10.1039/c9ce00960d
|View full text |Cite|
|
Sign up to set email alerts
|

Evaporation-driven manipulation of nanoscale brickwork structures for the design of 1D, 2D, and 3D microarrays of rectangular building blocks

Abstract: As children play with wooden building blocks, we would like to construct elaborate architectures through the one-by-one accumulation of nanocrystals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The fabrication of novel nanostructured materials via nanoparticle aggregation and self-assembly has proven to be one of the most promising superstructure formation pathways in the last decade [ 1 , 2 , 3 , 4 , 5 , 6 ]. The inherent particle-mediated nonclassical crystallization pathway of these processes has raised increasing scientific attention in more recent research [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Consequently, researchers have discovered that the behavior of a controlled aggregation and self-assembly can further be utilized to create astounding new materials with exciting properties [ 6 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The fabrication of novel nanostructured materials via nanoparticle aggregation and self-assembly has proven to be one of the most promising superstructure formation pathways in the last decade [ 1 , 2 , 3 , 4 , 5 , 6 ]. The inherent particle-mediated nonclassical crystallization pathway of these processes has raised increasing scientific attention in more recent research [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. Consequently, researchers have discovered that the behavior of a controlled aggregation and self-assembly can further be utilized to create astounding new materials with exciting properties [ 6 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, such systems containing NCs as building units can be characterized as colloidal crystals [35]. A special subspecies of these colloidal crystals are mesocrystals [36][37][38][39][40]. As soon as the NC subunits that build up a colloidal crystal are anisotropic and the alignment of those occurred on a long-range order, one can speak of a mesocrystal [41,42].…”
Section: Introductionmentioning
confidence: 99%
“…29 In the last few years, many research groups have reported on assembly techniques of micrometer-sized mesocrystals of platinum, magnetite, lead sulfide, and silver amongst other materials. 8,[30][31][32][33][34][35][36][37][38] They have shown remarkable structures of mesocrystals, which are perfectly regular and feature well-defined facets, like "classical" crystals. Commonly, nanocrystals are assembled to mesocrystals either via "drying mediated assembly methods" or via the "gas phase diffusion technique".…”
Section: Introductionmentioning
confidence: 99%